1986
DOI: 10.1002/ps.2780170607
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and confirmation of structure of four mammalian metabolites of dieldrin and endrin

Abstract: The first syntheses of syn-12-hydroxydieldrin, syn-12-hydroxyendrin and anti-12-hydroxyendrin have been accomplished by debenzoylation and epoxidation of three isomeric adduction products of hexachlorocyclopentadiene and 1,7,7-trinorborna-2,5-dien-7-yl benzoate. A third known metabolite of endrin, lZketoendrin, and a putative metabolite of dieldrin, lZketodieldrin, were prepared from the corresponding alcohols by oxidation with chromium trioxide. Characterisation of the three debenzoylated intermediates as syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The combined ether extracts were washed with water (2x10 ml), dried over anhydrous magnesium sulphate and evaporated to yield the crude alcohol (28 mg). Two recrystallisations from hexane yielded, as colourless crystals, pure 3-hydroxyisodrin (1,8,9,10,11,11 -hexachlor0-2,3-7,6-endo-2,1-7 ,8-endo-tetra-cyclo- Acetylation of XI at 100°C with acetic anhydride/pyridine/triethylamine yielded the acetate X quantitatively.…”
Section: -Hydroxyisodrin (Xi)mentioning
confidence: 99%
“…The combined ether extracts were washed with water (2x10 ml), dried over anhydrous magnesium sulphate and evaporated to yield the crude alcohol (28 mg). Two recrystallisations from hexane yielded, as colourless crystals, pure 3-hydroxyisodrin (1,8,9,10,11,11 -hexachlor0-2,3-7,6-endo-2,1-7 ,8-endo-tetra-cyclo- Acetylation of XI at 100°C with acetic anhydride/pyridine/triethylamine yielded the acetate X quantitatively.…”
Section: -Hydroxyisodrin (Xi)mentioning
confidence: 99%
“…Therefore, in order to show how computational chemistry can close some of the prevalent mechanistic gaps in biotransformation of pesticides, this work performed density functional theory (DFT) calculations to elucidate the fundamental molecular mechanism of CYP-dependent biotransformation of dieldrin, based on the experimental data available in the literature. Dieldrin was used as a model pesticide substrate, since this persistent organochlorine pesticide continues to be detected in a wide variety of environments and food chains, and thus has been the subject of numerous metabolic studies, although its use has been prohibited in many countries since the 1970s. As shown in Scheme , it was shown that dieldrin was metabolized in rats by liver microsomal CYP monooxygenases into 9-hydroxy-dieldrin via hydroxylation, and 3-ketone-dieldrin via dechlorination, and such reactions were inhibited by the monooxygenase inhibitor sesame, while no chemical or biochemical conditions have yet been found that can convert the former alcohol to the latter ketone .…”
Section: Introductionmentioning
confidence: 99%